ANALISIS PENUTUPAN LOKALISASI PROSTITUSI LORONG INDAH MARGOREJO KABUPATEN PATI - Dewi, Rahma Kusuma; Sardini, Nur Hidayat -; Martini, rina - (Journal of Politic and Government Studies, 2024)
The existence of the prostitution localization Lorong Indah Margorejo over the past two decades has become a social pathology in the midst of society and is considered to give a negative image to the Pati Regency. The existence of the localization also violates the laws and regulations regarding regional spatial plans because it stands on sustainable agricultural land which should not be used as a place to build buildings. The presence of instructions from the central government to implement Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) during Covid19 pandemic and encouragement from various parties is also an additional trigger for the local government of Pati Regency to carry out the closure of the prostitution localization Lorong Indah Margorejo. This study aims to analyze the dynamics of the localization closure process as well as the decision taken by the local government of Pati Regency after the closure. The type of research used descriptive qualitative method. The data collection techniques used were interviews and documentation. The results showed that the closure of the prostitution localization Lorong Indah Margorejo Pati went through a long dynamic. The closure process involved the Forkopimda of Pati Regency based on the legal basis that had been violated by the residents and the sociological basis in the hope of minimizing one of social pathology. Local government of Pati Regency continued to carry out the closure process until the demolition despite several obstacles during the closure process After the closure, the government did not provide compensation because it considered that the existence of the Lorong Indah itself had violated. The closure actually caused a new problem such as prostitution places that were fragments of Lorong Indah on the side of the road and their existence became more exposed. The local government of Pati Regency has according to procedures, but has not been able to apply the sociological approach with implementation of the sociology of government after the closure